A cross-sectional study of cancer patients visiting an outpatient Chinese medicine oncology clinic in Singapore - Wong, Kelly Hui Qin (Nanyang Technological University, 2020)
Cancer incidence rates have been on the rise in recent years. Despite treatments being developed continuously, cancer remains the principal cause of death. In Singapore, Traditional Chinese Medicine (TCM) is often reached out to as an additional treatment option. Doubts on the safety of concurrent usage of both medicines and the miscommunication between patients and doctors surrounding patients’ other medicine use are worrying problems. Hence, this paper aims to better understand cancer patient characteristics associated with TCM use and their reasons behind seeking TCM treatments, to enable provision of relevant advice for patients to make informed decisions. 165 responses were collected through self-administered or interviewer-administered survey. Majority were Chinese, female, married, not currently working, of lower education attainment and older age. Most patients sought TCM treatments for prevention purposes and to improve immunity. Contrary to belief, most only started TCM treatment (Chinese Herbal Medicine) after completion of their conventional treatments. Nevertheless, it is still essential for patients to inform their doctor about other medicine use for fear of adverse reactions. This study has provided insights on the use of TCM in oncology, but more needs to be done to bridge TCM and its scientific evidence to resolve the current dilemma.